Testbed on MANET (ToM): private testbed facility for MANET Experiment - Muchtar, Farkhana; Al-Adhaileh, Mosleh; Mohd Nordin, Ili Najaa Aimi; Mohd Hanif, Asyikin Sasha; Singh, Pradeep Kumar; Zubair, Ajoze Abdulraheem; Saheed, Ajibade Lukuman (Springer, 2019)
This article aims to share how to create a minimum MANET testbed facility as a requirement for evaluation of MANET research. Testbed facility that we have developed is called as Testbed on MANET or abbreviation ToM. We chose to use single board computer (SBC) to represent mobile devices in MANET. ToM facility and can be used either in a static mesh network or in a dynamic network topology, where each node in the testbed can move according to the needs of the researcher. To realize a real world node mobility in ToM, we use mobile robot technology and mobile robot that we have develop, where we named it as ToMRobot. Our experience in developing a ToM facility proves that with today’s technological developments, the private MANET testbed facility can be developed more easily at low cost.